USE OF ENTOMOPATHOGENIC FUNGI FOR THE BIOLOGICAL CONTROL OF TICKS IN CATTLE - Vilela, Rafaela Cristina de Oliveira; Vieira, Vanessa Amaro (Revista Interface Tecnológica, 2023)
The Rhipicephalus (Boophilus) microplus tick is an ectoparasite that represents major losses in Brazilian cattle farming. The aim of this study is to look at the use of entomopathogenic fungi as a form of biological control of bovine ticks, with an emphasis on research results, assessing the possibility of sustainable use as an alternative to current methods. The methodology adopted was a descriptive and exploratory literature review on the fight against the R. microplus tick, its life cycle and chemical and biological control methods. The use of fungi as biological control of ticks in cattle has been a sustainable strategy to traditional acaricidal chemotherapy. It increases the farmer’s profit in independence from the use of chemical control, reducing the problems of environmental impact, cost and outbreak of resistance. The fungus Metarhizium anisopliae has been one of the most studied pathogens, but still with modest results in tick control in the field.